Studi literatur: Efektivitas weaning ventilasi mekanik dengan pressure support ventilation (PSV) vs T-piece - Sungkono Sungkono; Riri Maria (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The effectiveness of mechanical ventilation weaning with pressure support ventilation (PSV) vs T-piece: A Literature studyBackground: Prolonged mechanical ventilation can increase the risk of infection, length of stay in the ICU, length of hospital stay, mortality, and cost of healthcare. The mechanical ventilation weaning process can be done using the pressure support (PSV) method or using a T-Piece. Purpose: Determine the effectiveness of the PSV vs T-Piece method in mechanical ventilation weaning.Method: The literature research uses electronic databases including PubMed, CINAHL, Proquest, and google scholar. Keywords for data search are using the keywords